Antimalarial and Antioxidant Activities of Ethanolic Stem Bark Extract of Terminalia macroptera in Swiss Albino Mice Infected with Plasmodium berghei - Ngouyamsa Nsapkain Aboubakar Sidiki; Noumedem Anangmo Christelle Nadia; Yamssi Cedric; Gamago Nkadeu Guy-Armand; Tientcheu Noutong Jemimah Sandra; Tako Djimefo Alex Kevin; Mounvera Abdel Azizi; Vincent Khan Payne (Journal of Parasitology Research)
Background. Reduction of oxidative stress during malaria infection is considered as being of great benefit so long as treatment and drug development approaches are concerned. This study had the aim of evaluating the antimalarial and antioxidant activities of the ethanolic extract of Terminalia macroptera in Swiss albino mice infected with the Plasmodium berghei NK65 strain. Methods. In vivo, the antiplasmodial activity of the plant ethanolic extract was tested in a four-day suppressive and curative assay using P. berghei in Swiss albino mice. The extract was administered to the mice at doses of 125, 250, and 500 mg/kg per day. Then, parameters, such as parasite suppression and survival time of the mice, were evaluated. Furthermore, the effect of plant extract on liver damage, oxidative stress indicators, and lipid profile changes in P. berghei-infected mice were studied. Results. Administration of T. macroptera significantly suppressed P. berghei infection by 55.17%, 70.69%, and 71.10% at doses of 125, 250, and 500 mg/kg, respectively, whereas chloroquine had 84.64% suppression relative to the untreated group 1% Dimethyl sulfoxide (1% DMSO) at day 4 (post-infection) in the four-day suppressive test. This suppression activity rate was dose-dependent. The curative test also presented a significant reduction in parasitemia and an extension of the survival time of the treated groups. Treatment of infected parasitized mice with the extract of T. macroptera had a significant (p<0.05) reduction in parameters, such as total protein, aspartate aminotransferase, and alanine aminotransferase. Infection may also lead to a significant increase in the enzymatic activity of liver catalase and superoxide dismutase compared with the normal control group. The non-enzymatic antioxidant activity in parasitized mice was significantly reduced in malondialdehyde and increased in glutathione and nitric oxide when compared with the normal control group. Conclusions. These findings support the ethnobotanical use of T. macroptera stem bark as an antimalarial remedy coupled with antioxidant activity. However, further in vivo toxicity tests are required to ascertain its safety.